Diseño de dispositivo para la autonomía de las personas en condición de discapacidad visual (2019)
People in a condition of visual disability are a vulnerable population, which is denied the possibility of having adequate mobility, by the changing platforms on which they move daily in Bogota, also because of the innumerable obstacles that come to be found . It is for this reason that the following question is created: How can the Industrial Design act, provide autonomy and safety so that people with visual disabilities on the platforms of Bogotá can perceive the obstacles?